2012
DOI: 10.1253/circj.cj-11-1285
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Complete Revascularization in Patients With Multivessel Coronary Disease in the Drug-Eluting Stent Era

Abstract: Background:The benefit of complete (CR) vs. incomplete revascularization (IR) with drug-eluting stent (DES), unlike with bypass grafting, is not well established in patients with multivessel coronary artery disease (MVD). Methods and Results Conclusions:In MVD patients treated with DES, CR was associated with the long-term benefit in reducing any or cardiac death and MI. The main beneficiaries of CR were those with diabetes, low ejection fraction and low eGFR. (Circ J 2012; 76: 1624 - 1630

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
1
16
0
3
Order By: Relevance
“…Comparing complete revascularization ( n = 1,188) with IR ( n = 2,053) among patients with multivessel CAD, Gao et al [45] found that IR was leading to a significantly higher rate of cardiac death. Chung et al [46] also reported that in comparison with IR, the adjusted hazard ratio of complete revascularization for cardiac death and MI was 0.39 (95% CI, 0.16–0.96). Furthermore, CAD patients with CKD have a higher risk of late restenosis, especially hemodialysis patients [47], which may lead to worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing complete revascularization ( n = 1,188) with IR ( n = 2,053) among patients with multivessel CAD, Gao et al [45] found that IR was leading to a significantly higher rate of cardiac death. Chung et al [46] also reported that in comparison with IR, the adjusted hazard ratio of complete revascularization for cardiac death and MI was 0.39 (95% CI, 0.16–0.96). Furthermore, CAD patients with CKD have a higher risk of late restenosis, especially hemodialysis patients [47], which may lead to worse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our data is consistent with that published by Schwartz et al ,7 Garcia et al 13 and Head et al 14 from post hoc analyses of clinical trials who described the impact of completeness of revascularisation on long-term (5 years) cardiovascular outcomes. To date, the only published observational ‘all-comers’ study reporting on patients with diabetes has a small (n=191) sample size15 in which CR was associated with better composite outcomes, but it was underpowered to show a statistically significant relationship with hard end points such as death.…”
Section: Discussionmentioning
confidence: 99%
“…In 3 (11,13,16) of the 5 studies, C-RV was associated with reduced R-RV. In 8 (6,9-11,13-16) of the 11 studies, C-RV was associated with reduced MAC(C)E. There were a number of important issues, however, in the aforementioned studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) of C-RV versus IC-RV in DES-PCI for MV-CAD (except for AMI) (Figure 1). First, "angiographic" (successful angioplasty of all diseased lesions in the major epicardial coronary vessels and their first degree side branches) and "proximal" C-RV definitions (successful angioplasty of all diseased proximal arteries) according to a study by Kim et al (18) are more accurate and clinically relevant.…”
mentioning
confidence: 99%
“…Our systematic search using keywords including "complete" or "completeness"; "incomplete" or "culprit"; "revascularization"; and "drug-eluting" identified 14 studies (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) summarized in Tables 1,2. The design of all studies was a non-randomized observational study, and all but one (13) studies reported adjusted HRs for outcomes of interest in "C-RV vs. IC-RV" or "IC-RV vs. C-RV".…”
mentioning
confidence: 99%
See 1 more Smart Citation